Addressing polysemy in bilingual lexicon extraction from comparable corpora. - Fišer, Darja; Kubelka, Ozren; Ljubešić, Nikola, informatičar (2012)
Addressing polysemy in bilingual lexicon extraction from comparable corpora
ENG